Assessing the Environmental Performance and Sustainability of National Agricultural Systems - Zucaro, Amalia; Mellino, Salvatore; Viglia, Silvio; Ulgiati, Sergio (Journal of Environmental Accounting and Management, 2026)
Agricultural systems are a crucial interface between human societies and nature, in that they “amplify” the human-controlled investments by concentrating natural energies of sun, rain, and nutrients and make them converge to food production. Even if gross economic value, labor and energy expenditures associated to agriculture are unlikely to ever represent a large fraction of the total performance of a national developed economy, yet the role of such a sector goes much beyond the actual food production and calls for higher attention by concerned policy makers. The evaluation of the dynamics and performance of agricultural systems must be carefully investigated from different sus- tainability points of view (energy, material, economic, environmental, social) to point out how the system and its main driving forces are evolving over time and how can they support a national economy. In this study we compare the agricultural systems of Scotland and Italy over time, by means of an integrated analysis model, SUMMA (Sustainability Multimethod Multiscale Assessment) capable to take into account different dimensions of the investigated systems. The final goal is to understand what are the steps of the investigated processes that are characterized by the lowest performances as well as how the system can be made more robust and resilient in spite of the existing problems (among which increasing energy and resource prices, de- creasing land quality, and decreasing marginal productivity).